Ureterotomia como tratamento da litíase ureteral em felino-Relato de caso - Bueno, Cynthia Marchiori [UNESP]; Rolemberg, Daniele Santos [UNESP]; Kihara, Mariana Tiai [UNESP]; Filgueira, Fabrícia Geovânia Fernandes [UNESP]; Minto, Bruno Watanabe [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Gonçalves DIas, Luis Gustavo Gosuen [UNESP]; Moraes, Paola Castro [UNESP] (My University, 2016)
The aim of this study was to report a case of ureteral calculi in a cat which was successful treated with surgical therapy ureterotomy. A 13 years old female cat, with clinical findings of cystitis for three years and presenting apathy, vomiting, reduced appetite, hypodipsia and normality in urination was referred to the Veterinary Hospital of Unesp-FCAV. Laboratory tests were performed (blood count and biochemical), and radiographic examination showed the presence of radiopaque structure in the left ureter, characterizing a partial ureterolithiasis. The animal was submitted to ureterotomy surgery for removal of uroliths. The removed material was sent for laboratory analysis, but could not be identified due to the sample size be insufficient. The patient continued with ureteral dilatation and hydronephrosis after surgery, presenting remission of clinical signs and normality of blood count and biochemical seven days after the operative procedure, occurring a reversal of the signs of chronic kidney disease, because the surgery was performed as soon as it was observed the presence of ureteral calculi. Medical treatment was important to give initial support for the patient, regulating the renal function and preventing serious injury. However, the ureterotomy was essential for the recovery of the patient, since it was observed remission of the clinical signs after the surgery and there were no postoperative complications.
Ureterotomy as treatment of ureter calculi in feline-Case report
Keywords: Cat; Surgery; Ureter; Urolith